A negative electrode material based on graphite lithium ion battery and preparation method thereof
By mixing N and P atoms in graphite negative materials, and loading tungsten phosphate nanoparticles to form a complex porous structure, solving the problem of insufficient electrochemical properties and low circulation life of graphite negative materials in high -mortivity discharge and low temperature environment , Achieve higher battery performance and stability.
Patent Information
- Application Number
- CN202411703262.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing graphite negative electrode materials have insufficient electrochemical performance in high-rate discharge and low temperature environments, and have low cycle life, structural expansion and uneven lithium ion insertion/exit.
Through the porous carbon formation process, the original bits are mixed with n atoms and P atoms to form a complex structure with pores, and loaded tungsten nanoparticles outside the porous carbon skeleton to improve the charging and discharge performance of the negative electrode material.
Improve the embedding and removal efficiency of lithium ions, enhance the reversibleness and cycle stability of the lithium ion battery, and improve the power density and charge efficiency of the battery.
Smart Images

Figure CN119191272B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials, and specifically refers to a negative electrode material based on a graphite lithium ion battery and a preparation method thereof. Background Art
[0002] Anode materials are a type of battery technology widely used in portable electronic devices, electric vehicles and energy storage systems. The selection of negative electrode materials is crucial to the performance of the battery (such as energy density, cycle life, charge and discharge rate, etc.); common electrode materials mainly include carbon materials, metal oxides and conductive polymers. Compared with the other two electrode materials, carbon materials have the advantages of large reserves, high specific surface area, and easy adjustment of surface structure, becoming the most important electrode material for various batteries. Among carbon materials, activated carbon, carbon nanotubes, graphene and carbon aerogel are mainly used. A single porous carbon material can control the electrochemical properties of the electrode material by adjusting the pore size, but the upper limit of the improvement of electrochemical performance is low, the rate performance is poor, the specific capacitance is low, and the cycle retention rate is low. Advantages of graphite as a negative electrode material: Excellent conductivity: Graphite has good conductivity, which helps to improve the charge and discharge efficiency of the battery; High theoretical capacity: The theoretical capacity of graphite is about 372 mAh / g, which can meet the needs of high energy density batteries; Mature production process: The extraction and processing technology of graphite materials is mature and the cost is relatively low; Although graphite has many advantages, its electrochemical performance still has certain shortcomings under high rate discharge and low temperature environments. In addition, as the number of charge and discharge cycles increases, graphite electrodes may experience structural expansion and uneven lithium ion insertion / extraction, which may affect the cycle life and stability of the battery. Summary of the invention
[0003] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a negative electrode material based on graphite lithium ion battery and a preparation method thereof, by in-situ doping N atoms and P atoms during the porous carbon formation process to form a complex structure with multiple pores, which is beneficial to improving the charge and discharge performance of the negative electrode material.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention proposes a method for preparing a negative electrode material based on a graphite lithium-ion battery, which specifically comprises the following steps:
[0005] S1. Dissolve 4,4'-diaminodiphenylmethane in dichloromethane, add triethylamine and mix well, place in an ice water bath, introduce nitrogen, and POCl 3The solution is added dropwise to the reaction system, and the reaction is stirred at a speed of 150-180 rpm. After 1-2 hours, the reaction temperature is increased to 90-120° C., and the reaction is refluxed for 4-6 hours to obtain a resin material. The resin material is placed in a beaker, OP-10 and formic acid are added, and the reaction is continuously stirred at a speed of 250-300 rpm. After 15-30 minutes, the mixture is placed in an oven and the temperature is increased to 70-80° C. After curing for 2-4 hours, the temperature is further increased to 100-120° C. and cured for 1-2 hours to obtain a phosphorus-containing resin foam.
[0006] 4,4'-Diaminodiphenylmethane and POCl 3 Phosphating reaction occurs in the presence of alkali (such as triethylamine) to form a resin material containing phosphorus chemical bonds; OP-10, as a surfactant, helps to form a uniform bubble structure, while formic acid may play a role in solubilization and pH adjustment, which is conducive to foaming; by controlling the temperature and stirring rate, the reactants gradually form a porous structure; the temperature-raising curing step in the oven further cross-links the material to form a thermosetting foam structure and improve the mechanical strength;
[0007] Preferably, in step S1, the mass concentration of 4,4'-diaminodiphenylmethane in dichloromethane is 0.1-0.15 g / mL;
[0008] Preferably, in step S1, the mass of triethylamine added is 5-8% of the mass of 4,4'-diaminodiphenylmethane; the addition of triethylamine can neutralize acidic byproducts such as hydrogen chloride generated during the reaction, protect the acid-base balance of the reaction system and inhibit side reactions;
[0009] Preferably, in step S1, the POCl 3 The solution is POCl 3 The POCl solution was dissolved in dichloromethane. 3 The volume fraction in dichloromethane is 12%-15%;
[0010] Preferably, in step S1, the 4,4'-diaminodiphenylmethane and POCl 3 The mass ratio between them is 1.2-1.5:1;
[0011] Preferably, in step S1, the added mass of OP-10 is 7%-12% of 4,4'-diaminodiphenylmethane;
[0012] Preferably, in step S1, the added mass of formic acid is 6%-8% of the mass of 4,4'-diaminodiphenylmethane;
[0013] S2, dissolving sodium tungstate and ethanolamine in DMF, introducing flowing nitrogen, stirring for 30-60 minutes under nitrogen atmosphere, adding thioacetamide, stirring and reacting at a speed of 280-300 rpm for 2-3 hours, adding hexadecyltrimethylammonium bromide, raising the reaction temperature to 110-130°C, reacting for 10-20 minutes, further raising the reaction temperature to 200-220°C, reacting for 30-60 minutes, cooling, filtering, and washing with anhydrous ethanol and deionized water to obtain tungsten sulfide nanoparticles;
[0014] Sodium tungstate, as a tungsten source, is dissolved in ethanolamine (MEA) and dimethylformamide (DMF) solvents; ethanolamine, as an alkaline solvent, can provide a nitrogen source and help the dissolution of sodium tungstate to form a tungsten coordination compound; ethanolamine, as an alkaline solvent, can provide a nitrogen source and help the dissolution of sodium tungstate to form a tungsten coordination compound;
[0015] Preferably, in step S2, the mass concentration of the sodium tungstate in DMF is 0.08-0.12 g / mL; DMF is a polar solvent that can effectively dissolve sodium tungstate and ethanolamine;
[0016] Preferably, in step S2, the added mass of ethanolamine is 2.4%-3% of the mass of sodium tungstate; ethanolamine not only acts as a solvent, but also may provide a nitrogen source in the subsequent reaction to promote the reaction;
[0017] Preferably, in step S2, the added mass of thioacetamide is 30%-40% of the mass of sodium tungstate; thioacetamide (TAA) as a sulfur source reacts with a tungsten source to provide sulfide, which promotes the reaction of sodium tungstate with sulfur to form tungsten sulfide; tungsten sulfide is a material with excellent photoelectric properties and high conductivity, and is widely used in catalysis, energy storage, nanoelectronics and other fields; thioacetamide as a sulfur source can effectively provide sulfur ions to react with tungsten ions to form tungsten sulfide;
[0018] Preferably, in step S2, the mass ratio of sodium tungstate to hexadecyltrimethylammonium bromide is 0.3-0.4:1;
[0019] S3, dispersing the tungsten sulfide nanoparticles prepared in step S2 in anhydrous ethanol, adding tungsten phosphate hydrate and mixing them thoroughly, raising the reaction temperature to 70-80°C, reflux reaction for 3-4 hours, placing in a vacuum drying oven, drying at 60-70°C for 5-7 hours, grinding, transferring to a tubular furnace, heating to 350-400°C at 10°C / min in a nitrogen atmosphere for sintering, sintering for 8-10 hours to obtain tungsten phosphosulfide nanoparticles;
[0020] The tungsten sulfide nanoparticles are dispersed in anhydrous ethanol, and tungsten phosphate hydrate is added. The tungsten phosphate hydrate provides a phosphorus source. Phosphorus interacts with the surface of tungsten sulfide to form tungsten phosphosulfide through coordination or chemical reaction. The phosphorus source is added to introduce phosphorus element and carry out phosphating reaction, so as to further improve the performance of tungsten sulfide. The introduction of phosphorus element can improve the catalytic performance, thermal stability and conductivity of the material, especially in high temperature and chemical corrosion environment, it has better oxidation resistance;
[0021] Preferably, in step S3, the mass concentration of the tungsten sulfide nanoparticles in anhydrous ethanol is 20-30 g / L;
[0022] Preferably, in step S3, the mass ratio between the tungsten sulfide and the tungsten phosphate hydrate is 1:0.5-0.7;
[0023] S4, placing the tungsten phosphosulfide nanoparticles prepared in step S3 in cyclohexane for full dispersion, immersing the phosphorus-containing resin foam prepared in step S1 in the reaction system, subjecting it to 500W ultrasonic treatment for 30-50min, transferring it to a high-pressure reactor, reacting it at 200-220°C for 20-28h, and after the reaction is completed, transferring it to a tubular furnace, raising the temperature to 300-350°C at 5°C / min, keeping it warm for 1-2h, and then continuing to raise the temperature to 500-550°C, keeping it warm for 1h, and after the reaction system is cooled to room temperature, repeatedly washing it with anhydrous ethanol and deionized water to obtain a negative electrode material;
[0024] Preferably, in step S4, the mass fraction of the tungsten phosphide nanoparticles in cyclohexane is 10-20 g / L;
[0025] By compounding tungsten phosphosulfide with phosphorus-containing resin foam, the high conductivity and catalytic activity of tungsten phosphosulfide and the lightweight and porous structure of resin foam can be combined to form a negative electrode material with excellent electrochemical and mechanical properties; the porous structure of the resin foam can provide support for tungsten phosphosulfide particles and increase their specific surface area and ion migration rate.
[0026] The present invention also provides a negative electrode material based on a graphite lithium-ion battery, which is prepared according to the above preparation method.
[0027] The beneficial effects achieved by the present invention are as follows:
[0028] The present invention provides a negative electrode material based on a graphite lithium ion battery and a preparation method thereof. The present invention can enhance the embedding and removal of lithium ions and enhance the reversibility of the lithium ion battery by in-situ synthesizing a high molecular polymer foam skeleton doped with a P element. Tungsten phosphosulfide nanoparticles are loaded on the outside of the high molecular polymer foam skeleton. After high temperature sintering, the formed lithium ion battery negative electrode material uses phosphorus-doped carbon as a porous carbon skeleton and loads high-performance tungsten phosphosulfide nanoparticles. The structure of the battery material can be optimized to reduce the energy barrier for the embedding / removal of lithium ions and improve the power density and charge and discharge efficiency of the battery. The polymer foam skeleton prepared by the present invention can introduce additional electronic states into the electronic structure of the material after being doped with P. The P element has The presence of additional electrons or unpaired electron holes can improve the conductivity of the carbon skeleton. The valence electron energy level of phosphorus is usually located in a lower energy band position and can participate in electron transfer, thereby forming more free carriers in the material and improving the conductivity of the material. In the process of porous carbon formation, N atoms and P atoms are in-situ doped to form a complex structure with multiple pores, which is beneficial to improving the charge and discharge performance of the negative electrode material. Tungsten sulfide has good conductivity and can shorten the electron conduction path, which helps to improve the performance of the battery. However, tungsten sulfide is prone to volume expansion and contraction during the charge and discharge process. The doping of phosphorus can improve the structural stability of tungsten sulfide nanoparticles and reduce the lattice damage of tungsten sulfide, thereby improving the long-term cycle stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a SEM image of the negative electrode material prepared in Example 1 of the present invention;
[0030] Figure 2 This is an enlarged SEM image of the surface structure of the negative electrode material prepared in Example 1 of the present invention;
[0031] Figure 3 The figure is a graph showing the rate performance results of the negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 at different current densities;
[0032] Figure 4 The cycle performance diagram of the negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 at 1 A / g.
[0033] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0035] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0036] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials and test strains used in the following examples are purchased from commercial channels unless otherwise specified.
[0037] The formic acid raw material is a formic acid aqueous solution, the formic acid raw material brand is Macklin's reagent, the product number is 767508, and the specification of the formic acid aqueous solution is 30% (w / w) in H 2 O / 500mL.
[0038] Example 1
[0039] This embodiment provides a method for preparing a negative electrode material based on a graphite lithium ion battery, which specifically includes the following steps:
[0040] S1. Accurately weigh 6.0 g of 4,4'-diaminodiphenylmethane and place it in a three-necked flask. Add 40 mL of dichloromethane to completely dissolve it. Then add 0.42 mL of triethylamine. Transfer the reaction system to an ice-water bath and stir it at 180 rpm. Pass flowing nitrogen into the reaction system. Accurately weigh POCl 3 2.4 mL was added to 20 mL of dichloromethane, stirred and dissolved, then added to the reaction system, stirred at 180 rpm for 1 hour, the temperature was raised to 90 ° C, and the reaction was continued for 6 hours. The water tolerance was 2.2 using turbidity measurement to obtain a resin material. The resin material was placed in a beaker, 0.42 g of OP-10 was added, and the resin was placed in a 40 ° C constant temperature water bath, stirred at a constant speed of 120 rpm, 1.2 mL of formic acid was added, and stirred at 250 rpm for 15 minutes, and then placed in an oven, the temperature was raised to 80 ° C, and after curing for 2 hours, the temperature was continued to be raised to 120 ° C. After curing reaction for 1 hour, it was washed with ethanol and dried to obtain a phosphorus-containing resin foam;
[0041] S2. Accurately weigh 5g of sodium tungstate and put it in a flask, add 60mL of DMF, stir until the sodium tungstate is completely dissolved, accurately weigh 0.12g of ethanolamine and add it to the reaction system, stir until the reaction system is evenly mixed, introduce flowing nitrogen, stir at 150rpm for 60min under nitrogen atmosphere, add 1.5g of thioacetamide, stir at 300rpm for 2h, add 1.6g of hexadecyltrimethylammonium bromide, place in an oil bath environment, raise the reaction temperature to 110℃, react for 20min, continue to raise the reaction temperature to 200℃, keep reflux reaction for 60min, quickly cool the reaction system with cold water, filter, take the solid, wash it repeatedly with anhydrous ethanol and deionized water three times in sequence, and vacuum dry it at 40℃ for 12h to obtain tungsten sulfide nanoparticles;
[0042] S3, take 5g of the tungsten sulfide nanoparticles prepared in step S2 and put them in a flask, add 250mL of anhydrous ethanol, put it on a magnetic stirrer, stir it at a speed of 500rpm, disperse the tungsten sulfide nanoparticles evenly in the anhydrous ethanol, add 3.5g of tungsten phosphate hydrate, continue stirring until the reaction system is in a uniform state, increase the reaction temperature to 80°C, react for 3h, after the reaction system is cooled to room temperature, transfer it to a vacuum drying oven, vacuum dry it at 70°C for 5h, take out the reactant for planetary ball milling, add 5mL of anhydrous ethanol to the abrasive to improve the dispersion performance, grind it for 12h at a ball-to-material ratio of 10:1, transfer it to a tubular furnace, introduce flowing nitrogen, increase the temperature to 350°C at 10°C / min for sintering, after 10h, cool it, and obtain tungsten phosphosulfide nanoparticles;
[0043] S4. Accurately weigh 2 g of the tungsten phosphosulfide nanoparticles prepared in step S3 and place them in 100 mL of cyclohexane for full dispersion. Immerse the phosphorus-containing resin foam prepared in step S1 in the reaction system, perform ultrasonic treatment at 500 W for 30 min, transfer to a high-pressure reactor, and react at 200 ° C for 28 h. After the reaction is completed, transfer to a tubular furnace, increase the reaction temperature to 300 ° C at 5 ° C / min, keep warm for 2 h, continue to increase the temperature to 500 ° C, keep warm for 1 h, wait for the reaction system to cool to room temperature, and repeatedly wash with anhydrous ethanol and deionized water to obtain a negative electrode material.
[0044] The present invention also provides a negative electrode material for a graphite lithium-ion battery prepared according to the above method.
[0045] Example 2
[0046] This embodiment provides a method for preparing a negative electrode material based on a graphite lithium ion battery, which specifically includes the following steps:
[0047] S1. Accurately weigh 6.0 g of 4,4'-diaminodiphenylmethane and place it in a three-necked flask. Add 50 mL of dichloromethane to completely dissolve it. Then add 0.58 mL of triethylamine. Transfer the reaction system to an ice-water bath and stir it at 150 rpm. Pass flowing nitrogen into the reaction system. Accurately weigh POCl 3 3.0mL was added to 20mL of dichloromethane, and after being fully stirred and dissolved, it was added to the reaction system, and the reaction was continued at a speed of 180rpm for 1h, and the temperature was raised to 100°C. After continuing the reaction for 6h, the water tolerance was measured by turbidity and was 2.2, and the resin material was obtained. The resin material was placed in a beaker, and 0.63g of OP-10 was added. It was placed in a 40°C constant temperature water bath, and stirred at a constant speed of 120rpm. 1.4mL of formic acid was added, and it was stirred at a speed of 300rpm for 15min, and then placed in an oven, and the temperature was raised to 70°C. After curing for 2h, the temperature was continued to be raised to 100°C. After curing reaction for 4h, it was washed with ethanol and dried to obtain phosphorus-containing resin foam;
[0048] S2. Accurately weigh 6 g of sodium tungstate and put it in a flask, add 60 mL of DMF, stir until the sodium tungstate is completely dissolved, accurately weigh 0.16 g of ethanolamine and add it to the reaction system, stir until the reaction system is evenly mixed, introduce flowing nitrogen, stir at 150 rpm for 60 min under a nitrogen atmosphere, add 2.1 g of thioacetamide, stir at 280 rpm for 3 h, add 1.7 g of hexadecyltrimethylammonium bromide, place in an oil bath environment, raise the reaction temperature to 120°C, react for 15 min, continue to raise the reaction temperature to 210°C, keep reflux reaction for 45 min, quickly cool the reaction system with cold water, filter, take the solid, wash it repeatedly with anhydrous ethanol and deionized water three times in sequence, and vacuum dry it at 40°C for 12 h to obtain tungsten sulfide nanoparticles;
[0049] S3, take 5g of the tungsten sulfide nanoparticles prepared in step S2 and put them in a flask, add 200mL of anhydrous ethanol, put it on a magnetic stirrer, stir it at a speed of 500rpm, disperse the tungsten sulfide nanoparticles evenly in the anhydrous ethanol, add 2.5g of tungsten phosphate hydrate, continue stirring until the reaction system is in a uniform state, increase the reaction temperature to 70°C, react for 4h, wait for the reaction system to cool to room temperature, transfer it to a vacuum drying oven, vacuum dry it at 70°C for 6h, take out the reactant for planetary ball milling, add 5mL of anhydrous ethanol to the abrasive to improve the dispersion performance, grind it for 12h at a ball-to-material ratio of 10:1, transfer it to a tubular furnace, introduce flowing nitrogen, increase the temperature to 400°C at 10°C / min for sintering, and after 8h, cool it to obtain tungsten phosphosulfide nanoparticles;
[0050] S4. Accurately weigh 2 g of the tungsten phosphosulfide nanoparticles prepared in step S3 and place them in 200 mL of cyclohexane for full dispersion. Immerse the phosphorus-containing resin foam prepared in step S1 in the reaction system, perform ultrasonic treatment at 500 W for 50 min, transfer to a high-pressure reactor, react at 220° C. for 20 h. After the reaction is completed, transfer to a tubular furnace, increase the reaction temperature to 330° C. at a rate of 5° C. / min, keep warm for 1.5 h, continue to increase the temperature to 550° C., keep warm for 1 h, wait for the reaction system to cool to room temperature, and repeatedly wash with anhydrous ethanol and deionized water to obtain a negative electrode material. The present invention also provides a negative electrode material based on a graphite lithium ion battery prepared according to the above method.
[0051] Example 3
[0052] This embodiment provides a method for preparing a negative electrode material based on a graphite lithium ion battery, which specifically includes the following steps:
[0053] S1. Accurately weigh 6.0 g of 4,4'-diaminodiphenylmethane and place it in a three-necked flask. Add it to 60 mL of dichloromethane and dissolve it completely. Then add 0.66 mL of triethylamine. Transfer the reaction system to an ice-water bath and stir it at 180 rpm. Pass flowing nitrogen into the reaction system. Accurately weigh 2.7 mL of POCl3 and add it to 20 mL of dichloromethane. After stirring and dissolving, add it to the reaction system. Continue stirring at 180 rpm for 2 hours, raise the temperature to 120 ° C, continue to react for 6 hours, and use turbidity to measure the water tolerance to be 2.2 to obtain a resin material. Place the resin material in a beaker and add OP-10 0.72 g, placed it in a constant temperature water bath at 40 ° C, stirred at a constant speed of 120 rpm, added 1.6 mL of formic acid, stirred at a speed of 250 rpm for 30 min, placed in an oven, raised the temperature to 80 ° C, cured for 1 h, continued to raise the temperature to 120 ° C, cured for 2 h, washed with ethanol, and dried to obtain a phosphorus-containing resin foam;
[0054] S2. Accurately weigh 7g of sodium tungstate and put it in a flask, add 60mL of DMF, stir until the sodium tungstate is completely dissolved, accurately weigh 0.21g of ethanolamine and add it to the reaction system, stir until the reaction system is evenly mixed, introduce flowing nitrogen, stir at 150rpm for 60min under nitrogen atmosphere, add 2.8g of thioacetamide, stir at 290rpm for 2.5h, add 1.75g of hexadecyltrimethylammonium bromide, place in an oil bath environment, raise the reaction temperature to 130℃, react for 10min, continue to raise the reaction temperature to 220℃, keep reflux reaction for 30min, quickly cool the reaction system with cold water, filter, take the solid, wash it repeatedly with anhydrous ethanol and deionized water three times in sequence, and vacuum dry it at 40℃ for 12h to obtain tungsten sulfide nanoparticles;
[0055] S3, take 5g of the tungsten sulfide nanoparticles prepared in step S2 and put them in a flask, add 160mL of anhydrous ethanol, put it on a magnetic stirrer, stir it at a speed of 500rpm, disperse the tungsten sulfide nanoparticles evenly in the anhydrous ethanol, add 3g of tungsten phosphate hydrate, continue stirring until the reaction system is in a uniform state, increase the reaction temperature to 80°C, react for 3h, wait for the reaction system to cool to room temperature, transfer it to a vacuum drying oven, vacuum dry it at 60°C for 7h, take out the reactant for planetary ball milling, add 5mL of anhydrous ethanol to the abrasive to improve the dispersion performance, grind it for 12h at a ball-to-material ratio of 10:1, transfer it to a tubular furnace, introduce flowing nitrogen, increase the temperature to 380°C at 10°C / min for sintering, and after 10h, cool it to obtain tungsten phosphosulfide nanoparticles;
[0056] S4. Accurately weigh 2 g of the tungsten phosphosulfide nanoparticles prepared in step S3 and place them in 200 mL of cyclohexane for full dispersion. Immerse the phosphorus-containing resin foam prepared in step S1 in the reaction system, perform ultrasonic treatment at 500 W for 40 min, transfer to a high-pressure reactor, react at 210° C. for 24 h. After the reaction is completed, transfer to a tubular furnace, increase the reaction temperature to 350° C. at a rate of 5° C. / min, keep warm for 1 h, continue to increase the temperature to 530° C., keep warm for 1 h, wait for the reaction system to cool to room temperature, and repeatedly wash with anhydrous ethanol and deionized water to obtain a negative electrode material.
[0057] The present invention also provides a negative electrode material for a graphite lithium-ion battery prepared according to the above method.
[0058] Comparative Example 1
[0059] This comparative example provides a negative electrode material and a preparation method thereof, which differs from Example 1 only in that S1 is not included in the preparation method, and the phosphorus-containing resin foam in S1 is replaced by melamine foam; the remaining components and component contents are the same as those in Example 1.
[0060] Comparative Example 2
[0061] This comparative example provides a negative electrode material and a preparation method thereof, which differs from Example 1 only in that S3 is not included in the preparation method, and the tungsten sulfide nanoparticles of the negative electrode material are not modified by phosphorus doping; the remaining components and component contents are the same as those in Example 1.
[0062] Experimental Example 1
[0063] In this experimental example, the microscopic morphology of the negative electrode material prepared in Example 1 was observed. A Hitachi S-4800 field emission scanning electron microscope was used, and the working voltage was set to 15 kV to observe the structure and morphology of the negative electrode material prepared in Example 1.
[0064] Figure 1 This is a SEM image of the negative electrode material prepared in Example 1 of the present invention. As shown in the figure, the negative electrode material prepared in Example 1 is supported by a polymer foam as a skeleton material, the skeleton surface is rough, and tungsten phosphide nanoparticles are loaded. Figure 2 This is an enlarged SEM image of the surface structure of the negative electrode material prepared in Example 1 of the present invention. As shown in the figure, the microstructure of the polymer foam skeleton is enlarged, and the microstructure of the tungsten phosphosulfide nanoparticles attached to the foam skeleton can be seen. The surface of the nanoparticles has a layered structure.
[0065] Experimental Example 2
[0066] This experimental example tests the polar electrochemical properties of the negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-2. The specific test methods include:
[0067] Construction of the battery: The negative electrode materials of the battery are respectively prepared by the negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 as the negative electrode, a metal lithium sheet is used as the counter electrode, diethyl carbonate (DEC) and ethylene carbonate (EC) are mixed in a volume ratio of 1:1, fluoroethylene carbonate is added as an additive at 10wt%, and LiPF is added at 1mol / L. 6 The electrolyte was mixed and assembled into a button cell in an argon atmosphere. After aging for 6 h, the electrochemical test was performed on a CHI760E electrochemical workstation in a frequency range of 100 kHz to 10 mHz.
[0068] The negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to rate performance tests at different current densities. Figure 3The figure is a graph showing the rate performance results of the negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 at different current densities. Figure 4 The cycle performance diagram of the negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 at 1A / g. As shown in the figure, the discharge specific capacity of the negative electrode materials prepared in Examples 1-3 at a current density of 0.1-5A / g is significantly higher than that of the negative electrode materials prepared in Comparative Examples 1 and 2. When the current density is restored to 0.1A / g, the corresponding average discharge specific capacity is restored to about 2200mAh / g, indicating that the capacity prepared in the present invention is increased during the activation process, and the negative electrode material has excellent reversibility; after the negative electrode material prepared in Comparative Example 1 is subjected to 10 cycles at a current density of 5A / g, when it is restored to 0.1A / g, the discharge specific capacity is not significantly restored, while the negative electrode material prepared in Comparative Example 2 has a certain degree of recovery, because the phosphorus-doped polymer foam skeleton has good electrical conductivity, the interlayer spacing of the tungsten phosphide nanoparticles in the negative electrode material prepared in the present invention is relatively wide, providing a channel for the rapid transmission of lithium ions, and the P element has electron holes, which increases the active sites of the negative electrode material, thereby improving the rate performance and cycle performance of the negative electrode material.
[0069] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
[0070] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a negative electrode material for a graphite lithium-ion battery, characterized in that: The specific steps include: S1. Dissolve 4,4'-diaminodiphenylmethane in dichloromethane, add triethylamine and mix well, place in an ice-water bath, introduce nitrogen, add POCl3 solution dropwise to the reaction system, stir at 150-180rpm for reaction, after 1-2h, raise the reaction temperature to 90-120℃, reflux for 4-6h to obtain a resin material; place the resin material in a beaker, add OP-10 and formic acid, stir and react at 250-300rpm for 15-30min, place in an oven and raise the temperature to 70-80℃, cure for 2-4h, then continue to raise the temperature to 100-120℃, cure for 1-2h to obtain a phosphorus-containing resin foam; S2, dissolving sodium tungstate and ethanolamine in DMF, introducing flowing nitrogen, stirring for 30-60 minutes under nitrogen atmosphere, adding thioacetamide, stirring and reacting at a speed of 280-300 rpm for 2-3 hours, adding hexadecyltrimethylammonium bromide, raising the reaction temperature to 110-130°C, reacting for 10-20 minutes, further raising the reaction temperature to 200-220°C, reacting for 30-60 minutes, cooling, filtering, and washing with anhydrous ethanol and deionized water to obtain tungsten sulfide nanoparticles; S3, dispersing the tungsten sulfide nanoparticles prepared in step S2 in anhydrous ethanol, adding tungsten phosphate hydrate and mixing them thoroughly, raising the reaction temperature to 70-80°C, reflux reaction for 3-4 hours, placing in a vacuum drying oven, drying at 60-70°C for 5-7 hours, grinding, transferring to a tubular furnace, heating to 350-400°C at 10°C / min in a nitrogen atmosphere for sintering, sintering for 8-10 hours to obtain tungsten phosphosulfide nanoparticles; S4. The tungsten phosphosulfide nanoparticles prepared in step S3 are placed in cyclohexane for full dispersion, the phosphorus-containing resin foam prepared in step S1 is immersed in the reaction system, subjected to 500W ultrasonic treatment for 30-50min, transferred to a high-pressure reactor, reacted at 200-220°C for 20-28h, and after the reaction is completed, transferred to a tubular furnace, raised to 300-350°C at 5°C / min, kept warm for 1-2h, and then continued to raise the temperature to 500-550°C, kept warm for 1h, and after the reaction system is cooled to room temperature, repeatedly washed with anhydrous ethanol and deionized water to obtain a negative electrode material.
2. The method for preparing a negative electrode material based on a graphite lithium ion battery according to claim 1, characterized in that: In step S1, the mass concentration of 4,4'-diaminodiphenylmethane in dichloromethane is 0.1-0.15 g / mL; the added mass of triethylamine is 5-8% of the mass of 4,4'-diaminodiphenylmethane; the POCl3 solution is a solution of POCl3 dissolved in dichloromethane, and the volume fraction of POCl3 in dichloromethane is 12%-15%.
3. The method for preparing a negative electrode material based on a graphite lithium ion battery according to claim 2, characterized in that: In step S1, the mass ratio between the 4,4'-diaminodiphenylmethane and POCl3 is 1.2-1.5:
1.
4. The method for preparing a negative electrode material based on a graphite lithium ion battery according to claim 3, characterized in that: In step S1, the added mass of OP-10 is 7%-12% of the mass of 4,4'-diaminodiphenylmethane; the added mass of formic acid is 6%-8% of the mass of 4,4'-diaminodiphenylmethane.
5. The method for preparing a negative electrode material based on a graphite lithium-ion battery according to claim 4, characterized in that: In step S2, the mass concentration of sodium tungstate in DMF is 0.08-0.12 g / mL.
6. The method for preparing a negative electrode material based on a graphite lithium-ion battery according to claim 5, characterized in that: In step S2, the added mass of the ethanolamine is 2.4%-3% of the mass of the sodium tungstate; the added mass of the thioacetamide is 30%-40% of the mass of the sodium tungstate.
7. The method for preparing a negative electrode material based on a graphite lithium-ion battery according to claim 6, characterized in that: In step S3, the mass concentration of the tungsten sulfide nanoparticles in anhydrous ethanol is 20-30 g / L; the mass ratio between the tungsten sulfide and tungsten phosphate hydrate is 1:0.5-0.
7.
8. The method for preparing a negative electrode material based on a graphite lithium-ion battery according to claim 7, characterized in that: In step S4, the mass concentration of the tungsten phosphosulfide nanoparticles in cyclohexane is 10-20 g / L.
9. A negative electrode material based on graphite lithium-ion battery, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Hollow foam material as well as preparation method and application thereof
CN108069725A
Heteroatom in-situ doped porous carbon composite lithium negative electrode and preparation method and application thereof
CN113991094A